Wood Vinegar Applications: Quality, Efficacy, and Commercial Prospects for SMEs - Andika, Riki; Didik Widiarta, I Putu Gede; Zalsabila, Ainun; Arinana, Arinana (West Science Interdisciplinary Studies, 2025)
Wood vinegar, scientifically defined as the condensation product of thermal decomposition (pyrolysis) of biomass rich in cellulose, hemicellulose, and lignin, presents a critical strategic step in efficient biomass waste management in Indonesia. Raw materials like coconut shells and palm oil waste are abundant, making their market potential highly promising. However, Indonesian Small and Medium Enterprises (SMEs) predominantly produce Grade 3 wood vinegar, which contains high levels of carcinogenic tar, hindering access to premium food-grade and pharmaceutical markets. This review aims to present a comprehensive report on the scientific characteristics and quality classification of wood vinegar, specifically analyzing the mechanism of action, effectiveness, and potential use of Grade 3 as an anti-termite agent (termiticide) and wood preservative, alongside its other advanced applications, such as food preservation, agricultural biopesticide, and latex coagulant. The method employed is a literature review, synthesizing data on chemical composition, purification standards (SNI and BPOM), and experimental findings on its multi-functional properties. The main conclusion is that Grade 3 wood vinegar proves highly effective as a termiticide, providing total wood protection and offering a safe, sustainable alternative to chemical wood preservatives. For food applications, rigorous purification to Grade 1 is essential to replace harmful practices like using formalin or borax. The novelty of this study lies in its integrated analysis of the technical efficacy (Grade 3 in termiticide) and the regulatory/commercial trade-off with food safety requirements (Grade 1), culminating in strategic recommendations for developing downstream purification technology for Indonesian SMEs
Keywords: Wood Vinegar; Pyrolysis; Termiticide; Coagulant; Pesticide